2012
DOI: 10.1007/s13204-012-0137-1
|View full text |Cite
|
Sign up to set email alerts
|

Mg/Al layered double hydroxide-Pt nanoparticle composite by delamination-restacking route

Abstract: Platinum nanoparticle intercalated magnesiumaluminum layered double hydroxide (LDH) composite was prepared by restacking the colloidal dispersion of organically modified LDH in the presence of preformed oleylamine capped platinum nanoparticles in n-butanol. The resultant nanocomposite was characterized using powder X-ray diffraction (PXRD), infrared (IR) spectroscopy, transmission electron microscopy (TEM), selected area electron diffraction and energy dispersive X-ray spectroscopy (EDX). The PXRD pattern of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Figure b,d depicts the average particle size distribution of LDH–[OH–C 6 H 4 COO] and CuNPs@LDH, with particle size ranging from 20 to 50 nm . The HRTEM study of CuNPs@LDH revealed that Cu nanoparticles are uniformly dispersed over the LDH platelets (Figure c,e) . Furthermore, HRTEM images shown in Figure e revealed an interplanar spacing of 0.25 nm, which is consistent with the interplanar distance of the Cu (111) crystallographic plane, which is consistent with the powder XRD results (Figure b). , Additionally, no diffraction patterns of Cu + species were found, which was consistent with the XRD results.…”
Section: Resultssupporting
confidence: 85%
“…Figure b,d depicts the average particle size distribution of LDH–[OH–C 6 H 4 COO] and CuNPs@LDH, with particle size ranging from 20 to 50 nm . The HRTEM study of CuNPs@LDH revealed that Cu nanoparticles are uniformly dispersed over the LDH platelets (Figure c,e) . Furthermore, HRTEM images shown in Figure e revealed an interplanar spacing of 0.25 nm, which is consistent with the interplanar distance of the Cu (111) crystallographic plane, which is consistent with the powder XRD results (Figure b). , Additionally, no diffraction patterns of Cu + species were found, which was consistent with the XRD results.…”
Section: Resultssupporting
confidence: 85%
“…Ni-Al LDH not only possess all the advantages of common LDH but also have the electrochemical activity because of the presence of a reversible one-electron redox couple, Ni(III)/Ni(II), which allows their application in electrochemistry area [29][30][31]. Electrochemical applications of LDH to electrochemical sensors, electrocatalysts, dye-sensitized solar cells and super capacitors were presented [32][33][34][35][36][37]. In the fuel cell applications, recently Ni-Al LDH has been reported to catalyze the electrooxidation of primary alcohols and sugars [38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches were used to synthesis of LDH and different methods have been proposed to modify electrode surfaces with LDH films; the most common one consists of depositing a fixed amount of a colloidal solution of the LDH, previously synthesized in bulk size [36,37], onto the electrodes [38][39][40][41]. A drawback of this method is the poor adhesion of the LDH films to the electrode surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…x OH 2 ] ( A n−1 ) x∕n , which comprise of divalent and trivalent metal cations, and interlayer exchangeable anions, represented by M 2+ and M 3+ , and ( A n−1 )x∕n , respectively (Nityashree and Menezes 2013). Water molecules are also found within the interlayers.…”
Section: +mentioning
confidence: 99%